Facet controlled growth mechanism of SnO2 (101) nanosheet assembled film via cold crystallization - Yoshitake Masuda (Nature Portfolio, 2021)
Abstract Cold crystallization of SnO2 was realized in aqueous solutions, where crystal growth was controlled to form SnO2 (101) nanosheet assembled films for devices such as chemical sensors. The nanosheets grew directly on a fluorine-doped tin oxide substrate without a seed layer or a buffer layer. The nanosheets had a thickness of 5–10 nm and an in-plane size of 100–1600 nm. Moreover, the large flat surface of the (101) facet was metastable. The thickness of the SnO2 (101) nanosheet assembled film was approximately 800 nm, and the film had a gradient structure that contained many connected nanosheets. TEM results revealed that the predominate branch angles between any two connected nanosheets were 90° and 46.48°, corresponding to type I and type II connections, respectively. These connections were consistent with the calculations based on crystallography. Crystallographic analysis clarified the characteristic crystal growth of the SnO2 (101) nanosheet assembled film in the aqueous solution. Furthermore, we demonstrate that the metastable (101) facet can be exploited to control the rate of crystal growth by adjusting the etching condition.